Pengaruh Beauty Influencer dan Korean Wave Terhadap Keputusan Pembelian Produk Skincare Korea (Studi Kasus Pada Masyarakat Kecamatan Medan Sunggal) - Febriani, Amelia; Tarigan, Eka Dewi Setia; Syahrial, Hery (Sains: Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine the influence of Beauty Influencers and the Korean Wave on purchasing decisions for Korean Skincare products in the people of Medan Sunggal District. The population in this study was the people of Medan Sunggal District with a total of 131,741 people. The sampling technique in this research was carried out by distributing questionnaires to 100 respondents. Data processing was carried out using multiple linear regression tests, validity tests, reliability tests, classical assumption tests, hypothesis tests and coefficient of determination using SPSS 26. The results of the study showed that Beauty Influencers had a positive and significant effect on purchasing decisions and the Korean Wave had a positive and significant effect on purchasing decisions. Beauty Influencers and the Korean Wave jointly influence purchasing decisions.Keywords: Beauty Influencer; Korean Wave; Purchasing Decisions